Reconstruction of chaotic signals with applications to chaos-based communications - Feng, Jiu Chao (Tsinghua University Press ; World Scientific, 2008)
"This book provides a systematic review of the fundamental theory of signal reconstruction and the practical techniques used in reconstructing chaotic signals. Specific applications of signal reconstruction methods in chaos-based communications are expounded in full detail, along with examples illustrating the various problems associated with such applications." "The book serves as an advanced textbook for undergraduate and graduate courses in electronic and information engineering, automatic control, physics and applied mathematics. It is also highly suited for general nonlinear scientists who wish to understand the basics of chaos-based signal and information processing. Written with numerous illustrative applications to capture the interest of casual readers, the book also contains adequate theoretical rigor to provide the necessary foundational as well as advanced material for serious researchers who are working or aspire to work in this area."--Jacket